2020
DOI: 10.2147/cmar.s266083
|View full text |Cite
|
Sign up to set email alerts
|

<p>Elevated Expression of ASXL2 is Associated with Poor Prognosis in Colorectal Cancer by Enhancing Tumorigenesis and Inducing Cell Proliferation</p>

Abstract: Colorectal cancer is one of the most common malignant tumors worldwide. ASXL2 is an enhancer of the trithorax and polycomb genes, which have been proven to act in many tumor types. The role of ASXL2 in the occurrence and development of tumors has been extensively studied in recent years. However, the relationship between ASXL2 and the prognosis of CRC is still unclear. Materials and Methods: In this study, quantitative real-time polymerase chain reaction (qRT-PCR), Western blot analysis and immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…These genes were not only highly upregulated by VGLL1 at the mRNA level but were also identified in the ChIP-seq analysis, indicating that VGLL1-TF complexes can interact with them directly. Interestingly, several studies have shown these genes to have roles in cancer cell proliferation, invasion, angiogenesis, and EMT transition (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Taken together, our findings provide additional mechanistic evidence that VGLL1 plays an important role in modulating the expression of specific genes involved in driving tumor progression.…”
Section: Vgll1 Expression Regulates Transcription Of Genes Involved I...supporting
confidence: 60%
“…These genes were not only highly upregulated by VGLL1 at the mRNA level but were also identified in the ChIP-seq analysis, indicating that VGLL1-TF complexes can interact with them directly. Interestingly, several studies have shown these genes to have roles in cancer cell proliferation, invasion, angiogenesis, and EMT transition (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Taken together, our findings provide additional mechanistic evidence that VGLL1 plays an important role in modulating the expression of specific genes involved in driving tumor progression.…”
Section: Vgll1 Expression Regulates Transcription Of Genes Involved I...supporting
confidence: 60%
“…ASXL2 encodes a member of a family of epigenetic regulators and is crucial in many biological processes. Alteration in this gene expression has been reported to be related to cancer in various tissue types (Cui et al, 2020; Medina et al, 2022; Wang et al, 2021), and variants of the ASXL2 gene have been reported to be associated with neurodevelopment, cardiac function, and osteoclastogenesis (Shashi et al, 2016). To date, five studies have reported patients with ASXL2 variants, and the variants and clinical features are summarized in Figure 2c and Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…ASXL2 is also associated with solid tumors. Elevated ASXL2 expression is linked to poor survival and is correlated with the prognosis of breast, colorectal, and pancreatic cancers [21,55,56], whereas its downregulation is associated with hepatocellular carcinoma [57]. In mice, ASXL2 loss leads to myeloid leukemia, suggesting a dual role in tumorigenesis.…”
Section: Tumor Suppressionmentioning
confidence: 99%